Penyuluhan Pemberian Latihan Brain Gym untuk Mengurangi Penurunan Kognitif pada Lansia di Posyandu Lansia Arjuna RW 3 Klampok Singosari Kabupaten Malang - Indah Aprilianti; Nungki Marlian Yuliadarwati; Ratna Vidia Amelia (Lembaga Pengembangan Kinerja Dosen, 2024)
As the elderly experience increasing age, it causes gradual physical and psychological decline, one of the problems faced by the elderly is cognitive impairment in the form of decreased memory. One effort to prevent cognitive decline in the elderly is to regularly do a brain gym. The aim of this community service is that the elderly can understand what cognitive decline is and how to prevent cognitive decline. The research method was carried out using a community service approach at the Arjuna Klampok Elderly Posyandu, Malang Regency by providing counseling about